Tinjauan Yuridis Terhadap Kewenangan Negara Dalam Regulasi Hak Kekayaan Intelektual Di Era Demokrasi Konstitusional - Fadli, Adrian; Lanontji, Muryanto; Dirawati, Dirawati (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Intellectual Property Rights (IPR) have strategic value in supporting the economic growth, creativity, and cultural preservation of a nation. In the context of a democratic state of law, the regulation of Intellectual Property Rights by the state is a constitutional responsibility that cannot be ignored. This study aims to analyze the form of state authority in regulating Intellectual Property Rights in a fair, effective, and constitutional manner. The research method used is normative juridical with statutory, conceptual, and case study approaches to several decisions of the Constitutional Court. The results showed that the implementation of state authority in the field of Intellectual Property Rights has not been optimal, both in terms of legal and institutional substance. The main challenges include weak law enforcement, lack of synergy between institutions, and the absence of maximum protection for communal cultural expressions. This research confirms that regulatory strengthening and institutional reform are needed to realize equitable Intellectual Property Rights protection and in accordance with the principles of constitutional democracy. The state must also balance the protection of individual rights with the public interest so that Intellectual Property Rights regulations do not cause social inequality in the digital era.